The Excited of Electromagnetic Waves for Langmuir Waves in Relativistic Plasma - A. S.Wahdain; J. A. Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The study of the excited nonlinear Langmuir waves has been obtained in relativistic plasma in a resonance beat frequency for two high frequency laser waves. In accordance to Vlasoy relativistic equation, we deduce a non-linear equation that illustrates the proceeding and behavior of the amplitude of exited Langmuir wave under resonant conditions and non-linear Schrödinger equation in her right term. On the basis of these two equations modulation and the kinetic resonance and we study the the effect of modulatior instability on the buildup of Langmuir wave